Technical and economic evaluation Separation of the separation of light olefins (Ethylene and Propylene) by using π-complexationwith silver salts - Salgado-Gordon, Hernando-José; Valbuena-Moreno, Gleidy (CT&F - Ciencia, Tecnología y Futuro, 2011)
Conventional processes for separation of ethylene and propylene until petrochemical grade are energy intensive; therefore, alternative separation processes, such as chemical affinity based technologies, are an interesting alternative for designing more sustainable processes. π-Complexation of the silver ion (Ag+) is one of these technologies. In this study, π-complexation is compared with the conventional technologies by evaluating from process and economic point of views, in order to determine whether they are feasible to be implemented at industrial scale in both grass-roots and existing units. Based on the results, the most promissory techniques to be applied are the Bulk Fluid Liquid Membrane (BFLM) in hollow fiber modules to separate ethylene/ethane, and absorption with an AgNO3 solution to separate propylene/propane. In addition, the implementation of hybrid processes, by combining conventional and chemical affinity technologies, provides a higher saving in the production cost when applied to revamp existing units to achieve both, reducing energy consumption, or increasing processing capacity.